KidsBrainIT: a new multi-centre, multi-disciplinary, multi-national paediatric brain monitoring collaboration - Lo, Tsz-Yan Milly; Piper, I.; Depreitere, B.; Meyfroidt, G.; Poca, M.; Sahuquillo, J.; Durduran, T.; Enblad, P.; Nilsson, P.; Ragauskas, A.; Kiening, Karl; Morris, K.; et al. (Intracranial Pressure & Neuromonitoring XVI, 2018)
OBJECTIVES: Validated optimal cerebral perfusion pressure (CPP) treatment thresholds in children do not exist. To improve the intensive care unit (ICU) management of the paediatric traumatic brain injury (TBI) population, we are forming a new paediatric multi-centre collaboration to recruit standardised ICU data for running and reporting upon models for assessing autoregulation and optimal CCP (CPPopt). - MATERIALS AND METHODS: We are adapting the adult BrainIT group's approach to develop a new Paediatric Brain Monitoring and Information Technology Group (KidsBrainIT), which will include a repository to store prospectively collected high-resolution physiological, clinical, and outcome data. In the first phase of this project there are 7 UK Paediatric Intensive Care Units, 1 Spanish, 1 Belgium, and 1 Romanian Centre interested in participating. In subsequent phases, we plan to open recruitment to other centres both within Europe, US and abroad. We are collaborating with the Leuven Group and plan to use their LAx (low-frequency autoregulation index), DATACAR (dynamic adaptive target of active cerebral autoregulation), CPPopt and visualisation methodologies. We also plan to use the continuous diffuse optical monitoring and tomography technology developed in Barcelona as an acute surrogate end-point for optimising brain perfusion. This technology allows non-invasive continuous monitoring of deep tissue perfusion and oxygenation in adults but its clinical application in infants and children with TBI has not been studied previously. - RESULTS: We report on the current status of setting up this new collaboration and also on pilot analyses in two centres which are the basis of our rationale for the need for a prospective validation study of CPPopt in children. Specifically, we demonstrated that CPPopt varied with time for each patient during their paediatric intensive care unit (PICU) stay, and the median overall CPPopt levels for children aged 2-6 years, 7-11 years and 12-16 years were 68.83, 68.09, and 72.17 mmHg respectively. Among survivors and patients with favourable outcome (GOS 4 and 5), there were significantly higher proportions with CPP monitoring time within CPPopt (p = 0.04 and p = 0.01 respectively). - CONCLUSIONS: There is a need and an interest in forming a multi-centre PICU collaboration for acquiring data and performing analyses for determining validated CPPopt thresholds in the paediatric TBI population. KidsBrainIT is being formed to meet that need.